2019
DOI: 10.1111/ijpo.12556
|View full text |Cite
|
Sign up to set email alerts
|

The influence of preschoolers' emotional and behavioural problems on obesity treatment outcomes: Secondary findings from a randomized controlled trial

Abstract: Summary Background Few studies have explored the influence of preschoolers' behavioural problems on obesity treatment. Objectives To assess emotional and behavioural problems before and after an obesity intervention and examine relationships between changes in child behaviour and changes in weight status. Method The study included 77 children (4‐6 years old, 53% girls, mean body mass index [BMI] z‐score of 3.0 [SD 0.6]) who participated in the More and Less Study, a randomized controlled trial. Families were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
7
0
3
Order By: Relevance
“…The lack of impact of attention concerns on FBBT treatment response was surprising given the impact of ADHD on the planning and organizational skills that are advantageous for health behavior change (Eiffener et al, 2019). Notably, a relatively small proportion (i.e., 5%) of youth in this study had elevated parent-reported attention concerns compared to the prevalence of ADHD in pediatric obesity populations (i.e., 8.3–23.6%; Cortese & Tessari, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of impact of attention concerns on FBBT treatment response was surprising given the impact of ADHD on the planning and organizational skills that are advantageous for health behavior change (Eiffener et al, 2019). Notably, a relatively small proportion (i.e., 5%) of youth in this study had elevated parent-reported attention concerns compared to the prevalence of ADHD in pediatric obesity populations (i.e., 8.3–23.6%; Cortese & Tessari, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Para intervenção correta e efetiva é importante detectar precocemente o ganho excessivo de peso na infância, pois o comportamento alimentar inicia-se na fase préescolar e influenciará os hábitos alimentares na adolescência e na vida adulta (MELO KM, et al, 2017). A família constitui o espaço mais íntimo de vivências, principalmente na faixa etária infantil, sendo o pilar para o desenvolvimento da criança e do futuro adulto, tendo papel fundamental na identificação e auxílio no tratamento dos distúrbios psicossociais (EIFFENER E, et al, 2019). A influência dos pais no comportamento infantil é essencial, pois as crianças tendem a se espelharem nos seus genitores, por isso, práticas alimentares saudáveis e a inserção de atividade física diária, já são consideradas um bom início para a prevenção da obesidade (SILVA GAP, et al, 2016).…”
Section: Discussionunclassified
“…Erste Studien haben gezeigt, dass sich psychische Probleme auf den Erfolg von Gewichtsreduktionsprogrammen bei Kindern und Jugendlichen auswirken, wenn auch die Befundlage aufgrund der unterschiedlichen Interventionen und Designs heterogen ist (Zusatzmaterial online). Harcourt et al (2019) berichteten, dass verstärkte Verhaltensprobleme sowie Hyperaktivität einen geringeren Gewichtsverlust während eines einjährigen ambulanten Gewichtsreduktionsprogramms prädizieren, während nach vergleichsweise kürzeren ambulanten Programmen (8 bis 10 Wochen) externalisierende Verhaltensprobleme mit einem höheren Gewichtsverlust direkt zu Interventionsende (Blomquist et al 2018) oder zur Jahreskatamnese (Eiffener et al 2019) einhergingen. Andere Autoren fanden keine Effekte initialer psychischer Probleme auf den Gewichtsverlauf zur Ein-bzw.…”
Section: Hintergrund Und Fragestellungunclassified
“…B. vermittelt über emotionales Essverhalten) und auch der Impulskontrolle betonen (Warschburger und Petermann 2008). Zum Einfluss der Veränderung psychischer Probleme auf den Gewichtsverlauf liegt gemäß dem Wissen der Autoren des vorliegenden Beitrags nur eine weitere Studie (Eiffener et al 2019) vor. Diese fand, dass sich eine Reduktion von Ängsten und Depressivität ungüns-tig auf die zeitgleiche Gewichtsreduktion auswirkt.…”
Section: Psychische Auffälligkeit Und Gewichtsverlaufunclassified